2013
DOI: 10.1111/ap.12007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Diabetes Self‐care, Metabolic Control, and Mental Health in Youth with Type 1 Diabetes

Abstract: The purpose of this study was to explore the psychosocial predictors of diabetes self‐care (adherence to care regimes), metabolic control (glycated haemoglobin), and mental health among rural‐ and urban‐dwelling youth with type 1 diabetes. One hundred and twenty three adolescents/young adults (aged 13−25 years, mean = 16 years, standard deviation = 3.8 years) with type 1 diabetes, 50 males and 73 females, completed questionnaires reporting on diabetes self‐care, metabolic control, mental health (negative affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 35 publications
5
33
1
Order By: Relevance
“…The adolescents’ ratings of their own degree of self-management of diabetes (self-care) were significantly and positively related to their metabolic control (lower HbA1c levels), and to how healthy they felt in general, supporting findings of several previous studies (e.g., [6,7]). Interestingly, their HbA1c levels did not correlate with their overall ratings of how healthy they felt, underscoring the difficulties of maintaining optimum glycaemic levels in the absence of early warning signals of unsafe levels.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The adolescents’ ratings of their own degree of self-management of diabetes (self-care) were significantly and positively related to their metabolic control (lower HbA1c levels), and to how healthy they felt in general, supporting findings of several previous studies (e.g., [6,7]). Interestingly, their HbA1c levels did not correlate with their overall ratings of how healthy they felt, underscoring the difficulties of maintaining optimum glycaemic levels in the absence of early warning signals of unsafe levels.…”
Section: Resultssupporting
confidence: 84%
“…This is a time when young people are also negotiating major physical, cognitive and psychological changes, and are at heightened vulnerability for engaging in risk taking behaviours (e.g., alcohol and other drug use) and for developing mental health problems [5,6]. While the rate of risk taking behavior has been found to be similar for adolescents with and without T1D, a general propensity toward risky behaviour in adolescents with T1D has been linked to poorer self care, and in turn to poor mental health and metabolic outcomes [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…This left a total of 35 articles included in the review. There were 15 (43%) descriptive or observational studies (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), 4 (11%) design or development studies (28-31), 3 (9%) quasi-experimental studies (2,32,33), 7 (20%) randomized controlled trials (34)(35)(36)(37)(38)(39)(40), and 6 (17%) qualitative studies (41)(42)(43)(44)(45)(46) included in the review.…”
Section: Methodsmentioning
confidence: 99%
“…If HbA1c levels can be maintained at below or about 7 %, there is likely to be fewer medical complications (American Diabetes Association, 2014 ). Hackworth et al ( 2013 ) also reported that an HbA1c assessment below 7.5 is an indicator of good control. Health educators and mental health counselors should remain aware of the child's HbA1c levels and stay in contact with the child's medical team so that they understand the child's medical needs and learn of best practices for managing the child's disease.…”
Section: Assessmentmentioning
confidence: 99%
“…Butwicka et al reported that children with diabetes are more likely to experience problems with substance use, depression, and anxiety. Depression may be the most common mental health problem for children with diabetes, followed by anxiety (Gonzalez et al, 2008 ;Hackworth et al, 2013 ). When depression levels are signifi cant, referral to a mental health professional with experience in diabetes management is recommended.…”
Section: Psychosocial and Emotional Functioningmentioning
confidence: 99%